Application of adaptive filters based on residue number system for satellite communications - Nikolay Ivanovich Chervyakov; Pavel Alekseyevich Lyakhov; Kirill Sergeyevich Shulzhenko (Наука. Инновации. Технологии, 2022)
The paper discusses the use of adaptive digital filters based on the Residue Number System for satellite communication systems. The signal distortions is an important problem of the practical use of satellites, which can significantly affect the quality of the processed signal and cause an error in the satellite positioning system. There is shown that the use of filters with inite impulse response using modular arithmetic for adaptive modeling of satellite orientation control systems in real time and recursive algorithm with Least Squares Method to configure the adaptive coefficients of the digital filter causes to minimize the output error between the monitoring system data and the satellite. The concept of the implementation of digital devices based on a Residue Number System, which can significantly improve the power consumption, performance, and resiliency of satellite communications is proposed.